Characterization of Catalytic Converter Made from Chrome-Plated Copper Plate Catalyst for Gasoline Motors - Irawan, RM Bagus; Sholecan, Achmad; Subri, M; Pantomy, Antonius (Universitas Muhammadiyah Jakarta, 2024)
This study characterizes copper (Cu) and chrome-plated copper (Cu-Cr) catalyst materials used in catalytic converters for gasoline engines. The objective is to investigate morphological and compositional changes resulting from exhaust gas emission testing. Scanning Electron Microscopy (SEM) coupled with Energy Dispersive X-ray Spectroscopy (EDX) was employed for microstructural analysis of the catalyst materials. The research examines morphological changes in Cu and Cu-Cr catalysts before and after exhaust gas emission testing, along with elemental composition alterations. Results indicate that exhaust gas exposure significantly alters the morphology and composition of both catalyst types. Morphologically, Cu catalyst particles originally flat with fine grains exhibited rougher, uneven surfaces with random grain formations and porosity post-testing. Similarly, Cu-Cr catalyst surfaces transformed from smooth to uneven, marked by darkened spots. Compositionally, Cu catalysts initially consisting of five elements (Cu 82.92%, O 5.96%, C 10.22%, Cl 0.60%, Si 0.29%) changed to include eight elements (Cu 70.65%, O 12.89%, C 12.85%, Cl 0.66%, Si 0.27%, N 1.74%, Al 0.27%, S 0.67%). Cu-Cr catalysts initially composed of three elements (Ni 87.65%, Cr 10.50%, C 1.85%) evolved to five elements (Ni 86.01%, Cr 6.56%, O 5.70%, O 1.42%, S 0.71%). These findings underscore the transformative effects of exhaust gas exposure on catalyst materials, influencing both their morphology and elemental composition, crucial for enhancing catalytic converter performance and durability in automotive applications.